The predictive contributions of environmental damage to the public management of conservation units: a case study of the Alto do Mucuri APA in Minas Gerais (Gestão & Regionalidade, 2024)
The relationship between governments and citizens can be the solution to get around the environmental crisis in which the world is inserted, mainly in the reformulation of the idea that natural resources are inexhaustible and can be deliberately exploited. The article sought to analyze the predictive contributions of environmental damage to public management in combating forest fires in the APA do Alto do Mucuri from 2014 to 2018. The Random Forest algorithm was used as a predictive technique in 138 Fire Occurrence Records (ROIs) of the conservation unit. The results show 14,729.92 hectares of burned vegetation in the region, predominantly of the Semideciduous Seasonal Forest type and analysis with better predictive capacity for low and moderate environmental damage. Thus, it is concluded the need to reformulate the ROI and the adoption of the Random Forest algorithm in decision-making in fighting forest fires.
Keywords: Conservation Unit; Forest Fires; Fire Occurrence Record; APA of Alto do Mucuri